Music and the Emotional Development of Children - Beus , Hana (Širjenje obzorij o poučevanju glasbe, 2025)
Music is something that accompanies us every day. It connects people, motivates, relaxes, and plays a crucial role in the healthy development of every individual. While numerous studies show that music affects cognitive and physical development, it is essential to emphasize its specific impact on emotions and their development. Music contributes to emotional development by influencing how we express ourselves, regulate our emotions, and develop socially. This chapter explores how and to what extent music influences the development of emotional and social competencies in children, what factors affect their development, and the role of a teacher in this process. It also provides tips and guidelines on how to support children in their emotional development.